Progressive changes in the retinal nerve fiber layer in patients with multiple sclerosis - Garcia-Martin, Elena; Pueyo, Victoria; Martin, Jesus; Almarcegui, Carmen; Ara, Jose R; Dolz, Isabel; Honrubia, Francisco M; Fernandez, Francisco J (European journal of ophthalmology, 2010)
To quantify changes in the retinal nerve fiber layer (RNFL) of patients with multiple sclerosis (MS) over a 1-year time period and to compare the ability of noninvasive diagnostic imaging devices and visual evoked potentials (VEP) to detect axonal loss in these patients. Eighty-one patients with MS underwent a complete ophthalmic examination that included assessment of visual acuity and color vision, refractive evaluation, visual field examination, optical coherence tomography (OCT), scanning laser polarimetry (GDx), and measurement of VEP. All the patients were re-evaluated after a period of 12 months in order to quantify any change in the RNFL. Only one randomly chosen eye from each patient was included in the study. Statistically significant differences between the 2 examinations were recorded for the overall mean and inferior RNFL thickness and the macular volume, as assessed by OCT, as well as for the temporal-superior-nasal-inferior-temporal average standard deviation provided by GDx. The greatest differences were obtained for the mean RNFL thickness (90.46 microm vs 85.96 microm). Changes in the optic nerve were detected by structural measurements but not by functional assessments. Axonal loss in the optic nerve of patients with MS is greater than that expected in healthy subjects, regardless of the presence of a previous optic neuritis.